anonymous
  • anonymous
Given A=integrate from 0 to 1 e^(-t^2) dt B=integrate from 0 to 1/2 e^(-t^2) dt compute the following dobule integral: 2 * integrate from -1/2 to 1 [integrate from 0 to x e^(-y^2) dy]dx as a function of A and B. Check that exists positives integers m and n and: I= m*A-n*B+e^(-1)-e^(-1/4) I tried reversing the integral order of the double integral to be able to compute easier, but it gave me: e^(-1)-e^(-1/4) + f(x) + c And if you made in the given order you got: e^(-1)-e^(-1/4) + f(y) + c And f(y) is where A and B came from, so I don't know how to solve this and... (to be continued)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
And I can't compute integrate from 0 to x [e^-(y^2)] dy I think I'll try using the definition of double integral and trying to work with the sumatories, but if anyone can help me I'll be happy. PD: Both constants haven't to be the same, it was a mistake to use "c" in both e^(-1)-e^(-1/4) + f(x) + c e^(-1)-e^(-1/4) + f(y) + k should be better.
anonymous
  • anonymous
Here are the ecuations in a easier way to read. \[A=\int\limits_{0}^{1}e^{-t^2}dt\] \[B=\int\limits_{0}^{1/2}e^{-t^2}dt\] \[I=2\int\limits_{-1/2}^{1}[\int\limits_{0}^{x}e^{-y^2}dy]dx\] \[I = mA -nB +e^{-1}-e^{-1/4}\]
anonymous
  • anonymous
I had an idea. First I define: f(x)=\[f(x)=\int\limits_{0}^{x} e^{-y^2}dy\]e^(-y^2) I'm evaluating the integral of \[e^{-y^2}\] between 0 and x, and this antiderivate in 0 is a constant, so: \[f'(x)=e^{-x^2}\] Then I can use integration by parts: \[2\int\limits_{}^{}f(x)dx=2(xf(x)-\int\limits_{}^{}xf'(x)dx)\] \[2\int\limits_{}^{}xf'(x)dx=2\int\limits_{}^{}xe^{-x^2}dx=-e^{-x^2}\] You can solve the last part with a simple substitution, -x^2=u \[2\int\limits_{}^{}xe^{-x^2}dx=2\int\limits\limits\limits_{}^{}xe^{-u^2}/(-2x)du=-\int\limits\limits_{}^{}e^{u}du=-e^u=-e^{-x^2}\] Then: \[2\int\limits_{}^{}f(x)dx=2xf(x)-(-e^{-x^2})\] \[2\int\limits\limits_{-1/2}^{1}f(x)dx=2(1)f(1)+e^{-1^2}-(2(-1/2)f(-1/2)+e^{-(-1/2)^2})=\] \[2f(1)+e^{-1^2}+f(-1/2)-e^{-(1/4)}\] \[B=\int\limits_{-1/2}^{0}e^{-t^2}dt \rightarrow -B=\int\limits_{0}^{1/2}e^{-t^2}dt\] Because t is squared, so \[e^{-t^2}=e^{-(-t^2)}\] And the function is simetric. Then \[f(-1/2)=-f(1/2)\] \[2f(1)+e^{-1}-f(1/2)-e^{-(1/4)}=2A-B+e^{-1}-e^{-(1/4)}\] Then m=2 and n=1

Looking for something else?

Not the answer you are looking for? Search for more explanations.